Left ventricular reverse remodelling and its predictors in non-ischaemic cardiomyopathy - Hnat, Tomas; Veselka, Josef; Honek, Jakub (ESC heart failure, 2022)
Adverse remodelling following an initial insult is the hallmark of heart failure (HF) development and progression. It is manifested as changes in size, shape, and function of the myocardium. While cardiac remodelling may be compensatory in the short term, further neurohumoral activation and haemodynamic overload drive this deleterious process that is associated with impaired prognosis. However, in some patients, the changes may be reversed. Left ventricular reverse remodelling (LVRR) is characterized as a decrease in chamber volume and normalization of shape associated with improvement in both systolic and diastolic function. LVRR might occur spontaneously or more often in response to therapeutic interventions that either remove the initial stressor or alleviate some of the mechanisms that contribute to further deterioration of the failing heart. Although the process of LVRR in patients with new-onset HF may take up to 2 years after initiating treatment, there is a significant portion of patients who do not improve despite optimal therapy, which has serious clinical implications when considering treatment escalation towards more aggressive options. On the contrary, in patients that achieve delayed improvement in cardiac function and architecture, waiting might avoid untimely implantable cardioverter-defibrillator implantation. Therefore, prognostication of successful LVRR based on clinical, imaging, and biomarker predictors is of utmost importance. LVRR has a positive impact on prognosis. However, reverse remodelled hearts continue to have abnormal features. In fact, most of the molecular, cellular, interstitial, and genome expression abnormalities remain and a susceptibility to dysfunction redevelopment under biomechanical stress persists in most patients. Hence, a distinction should be made between reverse remodelling and true myocardial recovery. In this comprehensive review, current evidence on LVRR, its predictors, and implications on prognostication, with a specific focus on HF patients with non-ischaemic cardiomyopathy, as well as on novel drugs, is presented.
Keywords: Echocardiography; Left ventricular reverse remodelling; Cardiomyopathies; Predictors; Ventricular Remodeling; Humans; Non-ischaemic cardiomyopathy; Heart failure; Heart Failure; lidé; funkce levé komory srdeční; srdeční selhání; remodelace komor; echokardiografie; Cardiac remodelling; Ventricular Function, Left; Reverse remodelling; kardiomyopatie